A study on prevalence of cardiovascular disease related risk factors among tribal population in a block of West Bengal - Santra, Sutanuka; Shrivastava, Prabha (International Journal Of Community Medicine And Public Health, 2019)
Background: Non communicable diseases (NCDs) refer to chronic diseases of long duration and generally with slow progression. NCDs are affecting Indian population, both in urban and rural areas. Cardiovascular disease (CVD), one of the major NCDs is the leading cause of death worldwide. The rising prevalence of behavioral and anthropometric risk factors for these lifestyle diseases is postulated to be the cause for the alarming increase of NCDs including CVD. Prevalence of cardiovascular diseases is also increasing in tribal population. Objective of this study was to assess the prevalence of risk factors associated with cardiovascular diseases among the tribal population aged 18 years and above. Methods: A community based, observational, descriptive study was conducted at Kharagpur-II block of Paschim Medinipur district, West Bengal from August 2013 to July 2014 among 540 tribal population aged 18 years and above selected by cluster random sampling method. Results: About 64% individuals were addicted to tobacco product. Prevalence of current smoking and tobacco chewing was 9.1% and 60.2% respectively. Prevalence of current alcohol consumption was 48.9%. About 91% individuals took extra salt with meal. Prevalence of overweight and obesity was 7.8% and 3.5% only according to WHO recommended classification for Asian population. However, higher level of physical activity was found among the study population. Conclusions: The study revealed high prevalence of extra salt intake, tobacco and alcohol consumption among the study population which may endanger their life by increasing the risk of cardiovascular disease.